Goldenhar Syndrome Presenting As Squamosal Chronic Otitis Media - Ambewadi, Ravi; Bhat, Vikram Kemmannu; Salian, Prajna Laxman (Annals of Otology and Neurotology, 2020)
Goldenhar syndrome is a rare congenital anomaly involving the eye, ear, vertebra, and the mandible. This anomaly presenting primarily to the ENT outpatient clinic with ear discharge and cholesteatoma is still rarer. Here we describe one such rare case that was a challenge to diagnose as well as manage. We also discuss the various problems in the management and highlight the need for a multispecialty approach to tackling the various pathologies in such a case.
Keywords: hearing loss; otitis media; Goldenhar syndrome